IMPLEMENTASI PROGRAM SIPELANDUKILAT DALAM PENINGKATAN PELAYANAN PUBLIK DI WILAYAH PERBATASAN DAN PEDALAMAN - Serly Wulandari; Anisha Widowati (Jurnal Kebijakan Pemerintahan, 2023)
Abstract Nunukan Regency has a border and interior area which is one of the causes of the difficulty in recording population administration, so it gave birth to a program called The fast Population Administration Service System for Border Area and Outback or SIPELANDUKILAT. This research aims to know the implementation of the SIPELANDUKILAT program in serving population administration records for border and inland communities. This research used a descriptive design with qualitative methods and data collection techniques through interviews, observation and documentation—data analysis techniques using data reduction and data presentation to conclude. The results showed that implementing the SIPELANDUKILAT program in Nunukan Regency, in general, has been going quite well but not optimal. Based on the publishing results of 4.354 administrative population documents from the planned document target of 700-1500 documents and four variable analysis based on Edwards III Theory, this can be found. The Nunukan Regency Population and Civil Registration Office have carried out the communication dimension directly through a pick-up system, but the information is not evenly distributed. Resource dimension, the designated implementing team are the experts in their field. However, in terms of quantity, there is still insufficient to implement the SIPELANDUKILAT program. Disposition dimension, exercising team commitment is shown by discipline and loyalty in carrying out the program to run on time. Bureaucratic structure dimensions, the SIPELANDUKILAT program has been stated in the Decree of the Governor of North Kalimantan Province Number: 188.44/K.353/2020 the Year 2020. Keywords: Population Administration, Implementation, Services, SIPELANDUKILAT Program